2021
DOI: 10.1172/jci.insight.146604
|View full text |Cite
|
Sign up to set email alerts
|

An inducible Cre mouse for studying roles of the RPE in retinal physiology and disease

Abstract: The retinal pigment epithelium (RPE) provides vital metabolic support for retinal photoreceptor cells and also is an important player in numerous retinal diseases. Gene manipulation in mice using the Cre-LoxP system is an invaluable tool for studying the genetic basis of these retinal diseases. However, existing RPE-targeted Cre mouse lines have critical limitations that restrict their reliability for studies of disease pathogenesis and treatment, including mosaic Cre expression, inducer-independent activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…This is consistent with preservation of reduced ERG expression in a subset of KCNJ13CKO ko/ko, VMD2-Cre +/+ mice. In addition, it has been shown recently that Cre expression with this model shows some leakiness with expression in other retinal cells than the RPE ( Chen et al, 2021 ; Choi et al, 2021 ). This is also apparent in Figure 5B , in which Cre expression is seen not only in the RPE but also the GCL and INL.…”
Section: Discussionmentioning
confidence: 83%
“…This is consistent with preservation of reduced ERG expression in a subset of KCNJ13CKO ko/ko, VMD2-Cre +/+ mice. In addition, it has been shown recently that Cre expression with this model shows some leakiness with expression in other retinal cells than the RPE ( Chen et al, 2021 ; Choi et al, 2021 ). This is also apparent in Figure 5B , in which Cre expression is seen not only in the RPE but also the GCL and INL.…”
Section: Discussionmentioning
confidence: 83%
“…We generated a new Rpe65 CreERT2 Cre driver line with a genomic design resembling a previously published model [ 50 ]. The Rpe65 CreERT/ + 2 mice showed normal retinal function and morphology, as assessed by ERG and histological sections, respectively (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2C, D). Previously, Choi et al [ 50 ] demonstrated that the Rpe65 CreERT2 homozygous mice exhibited reduced RPE65 isomerase levels compared to heterozygous and WT mice. However, we did not observe a decrease in RPE65 expression in our mice (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ADAM17 is a member of the adamalysin family that are responsible for the shedding (ectodomain cleavage) of cell membrane proteins. ADAM17 expression has been shown in endothelial cells and different cell types of the CNS [ 24 , 45 ]. In mammals, the forebrain, where optic vesicle formation is ADAM17-positive, suggests the necessity of ADAM17 for retinal morphogenesis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A day before ERG testing, the mice were dark-adapted for > 12 h. Animal handling was performed under dim red light. Anesthetized mice were positioned on the thermal pad (37 ± 1 °C), and the stimulator was placed on the surface of the cornea with the largest contact surface, according to the protocol suggested by the instructor [ 24 ]. The dark-adapted ERG and OPs were stimulated with an ascending flash series (intensity 0.01, 0.1 and 1 cd.s/m 2 ; frequency 1 Hz), and the signal waves were acquired from 50 ms pre-trigger to 300 ms post-trigger.…”
Section: Methodsmentioning
confidence: 99%